The Influence of International Scope on the Relationship Between Patented Environmental Innovations and Firm Performance. (February 2017) - Bermúdez-Edo, Maria; Hurtado-Torres, Nuria E.; Ortiz-de-Mandojana, Natalia
The literature on the natural-resource-based view of firms has mostly focused on the positive relationship between financial performance and environmental innovation. The present study extends this research by addressing recent calls to identify the specific managerial approaches that affect a firm's ability to financially benefit from an innovative environmental strategy. In particular, the focus is on how the selected international scope of patented environmental innovations affects a firms' financial performance. The sample used included a 5-year data panel of 3, 087 environmental patent applications by the 79 Information and Communication Technology firms in the Financial Times Global 500 firms list. The findings indicate that the geographical scope of the exploitation of environmental patents increases the positive relationship between patented environmental innovation and financial performance whereas the geographical scope of knowledge sourcing of environmental patents does reduce this performance.